Edukasi Pentingnya Menabung sejak Dini di Dusun Lilin - Yulistiani, Ni Wayan; Suardana, I Ketut Putu; Laksmi, Ida Ayu Nyoman Widia; Yasa, I Komang Widya Purnama (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
The program “Financial Education: The Importance of Saving from an Early Age in Lilin Hamlet” was implemented as a community engagement initiative aimed at fostering financial awareness and saving habits among children and adolescents in rural areas. Using a participatory-educational approach, the program consisted of four stages: planning, socialization, saving practice, and evaluation. A total of 27 participants, ranging from elementary to high school students, took part in the activities held at the Pasraman Kilat community learning center. The sessions were designed to be interactive through discussions, visual media, and hands-on saving activities using simple piggy banks. The results indicated a notable improvement in financial understanding and behavior, with 48.15% of participants saving regularly during the program. The amount saved ranged between IDR 17,000 and IDR 28,000. The program not only enhanced financial literacy but also cultivated responsibility and self-discipline among participants. A participatory learning environment was found to be a key factor in sustaining engagement and behavioral change. These findings suggest that practice-based financial education embedded in local cultural values can serve as an effective strategy to instill early saving habits and strengthen financial literacy within rural communities.